Financing Retirement in the European Union - Lans Bovenberg (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper explores how EU countries can address various challenges (including the aging of the population) affecting their systems of old-age income support. It presents two scenarios illustrating the most important uncertainties surrounding the major developments that affect the pension systems of the EU. To diversify these risks, EU governments should act on several fronts. In addition to the formation of human capital (especially that of children), employment (especially that of older workers) should be boosted. This calls for social insurance reform with more emphasis on individual saving schemes. Pension schemes should be more explicit about how they share demographic and other risks. Countries that currently rely heavily on public pay-as-you-go (PAYG) schemes should stimulate private pensions by gradually reducing PAYG benefits collected by high-income earners, by issuing new financial instruments, and by conducting intergenerational risk sharing through the tax system.
Keywords: 330